1990
DOI: 10.1302/0301-620x.72b5.2211750
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty after fracture of the acetabulum. Long-term results

Abstract: We made a retrospective study of 55 primary total hip arthroplasties in 53 patients with a history of previous acetabular fracture. The mean follow-up was 7.5 years and the average age at fracture was 48.7 years. The incidence of radiographic femoral loosening (29.4%), symptomatic loosening (15.7%), and femoral revision (7.8%) were similar to those previously reported at 10 years for routine arthroplasties by Stauffer (1982). On the acetabular side, the incidence of radiographic loosening (52.9%), symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
1
15

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(106 citation statements)
references
References 0 publications
4
86
1
15
Order By: Relevance
“…In addition, most surgeons employ restricted weightbearing for 6 to 12 weeks after acetabular fracture surgery, something that elderly patients are often not able to adhere to, resulting in secondary loss of fracture reduction. There is little in the literature suggesting good outcomes with fixation of the elderly acetabular fracture [2,11,13,31,35]. We therefore evaluated a treatment algorithm that involved fracture fixation plus THA and immediate weightbearing in selected older patients with acetabular fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most surgeons employ restricted weightbearing for 6 to 12 weeks after acetabular fracture surgery, something that elderly patients are often not able to adhere to, resulting in secondary loss of fracture reduction. There is little in the literature suggesting good outcomes with fixation of the elderly acetabular fracture [2,11,13,31,35]. We therefore evaluated a treatment algorithm that involved fracture fixation plus THA and immediate weightbearing in selected older patients with acetabular fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these methods involve significant delays to mobilization, and in either case, if the patient survives and has hip pain, a THA often is carried out electively at a later date. Other options have been reported, including early fixation and delayed arthroplasty or acute arthroplasty [1,2,13,16,21,25,31,35], but we are not aware of any series of such patients where initial management has allowed immediate full weightbearing.…”
Section: Introductionmentioning
confidence: 99%
“…61,83,84 Delayed hip arthroplasty following acetabular fractures with central dislocation may follow either conservative, 56,85 or operative fracture treatment. 13,63,[86][87][88] Several authors have suggested that open reduction and internal fixation of fractures may preserve bone stock and allow easier THA if required at a later date, 13,63,[86][87][88] whereas others feel that it is not necessary and complicates later arthroplasty due to dense scar tissue, heterotopic ossification, the need for hardware removal in many instances, increased operative time, blood loss, transfusion requirements and potential occult infection. 15,16,63,81,84,[87][88][89][90] The results of THA for all types of acetabular fractures have been historically inferior to those performed for primary osteoarthritis due to higher rates of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,63,81,84,[87][88][89][90] The results of THA for all types of acetabular fractures have been historically inferior to those performed for primary osteoarthritis due to higher rates of aseptic loosening. 14,86,87,90,91 This has been attributed to residual acetabular deformity and bony deficiency, which often require bone grafting and can make anatomic restoration of the hip centre difficult; younger age and weight over 80 kg. 63,[86][87][88][89][90][91][92] Using cemented acetabular cups Romness and Lewallen 86 reported radiographic loosening in 52.9%, which was symptomatic in 27.5% and progressed to revision in 13.7% at 7.5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation